2020
DOI: 10.3389/fpsyg.2020.577708
|View full text |Cite
|
Sign up to set email alerts
|

From Shattered Goals to Meaning in Life: Life Crafting in Times of the COVID-19 Pandemic

Abstract: The novel COVID-19 pandemic has created an extraordinary situation for our generation, with many countries being on lockdown. With this, new situation comes many psychological challenges not only for health care workers and people suffering from COVID-19 but also for the general population. Adapting to the new situation can be demanding. Experts have suggested that emotions during this situation are very similar to grief, and people experience emptiness and sadness about the loss of their normal lives, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 31 publications
2
102
0
3
Order By: Relevance
“…However, it is suggested that psychological interventions aimed at re-signifying experiences and finding new meaning in their lives could help to cushion the negative effects of the pandemic situation. For example, it has been proposed that life crafting interventions could offer a way to help people cope and renew their sense of life (De Jong et al, 2020 ). In relation to the cluster analysis between purpose in life and COVID affectation, three clusters are obtained with the same structure as the clusters obtained with the gratitude variables, in which the group with the worst affectivity and meaning of life, categorizes—in a biased way—COVID affectation, while another group that indicates that it feels worse since the pandemic, obtained good affectivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is suggested that psychological interventions aimed at re-signifying experiences and finding new meaning in their lives could help to cushion the negative effects of the pandemic situation. For example, it has been proposed that life crafting interventions could offer a way to help people cope and renew their sense of life (De Jong et al, 2020 ). In relation to the cluster analysis between purpose in life and COVID affectation, three clusters are obtained with the same structure as the clusters obtained with the gratitude variables, in which the group with the worst affectivity and meaning of life, categorizes—in a biased way—COVID affectation, while another group that indicates that it feels worse since the pandemic, obtained good affectivity.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, several authors and scientists call for new reflections on the meaning of life and how to cope with the pandemic in a transformational and healthy way (Rodríguez-Rey et al, 2019 ; De Jong et al, 2020 ; Wong, 2020a , b ). In this part of the article, the meaning of Camus' life and work is reflected with regard to the Covid-19 pandemic.…”
Section: The Meaning Of Camus In Times Of Covid-19mentioning
confidence: 99%
“…In the dawn of Covid-19 and the realization of the need for new approaches to deal with challenging life situations, role models are needed to respond to the question of how to deal with uncertainty, loneliness, defining a meaningful life, and collective and transformational ways of coping (Rodríguez-Rey et al, 2019 ; De Jong et al, 2020 ; Wong, 2020a , b ; World Economic Forum, 2020 ). The suffering and pain experienced in daily life by individuals (Frankl, 1959 ) needs to be understood within the context of greater, global meaning-making (Baumeister, 1991 ) and the transformation of stressful events (Park, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, under favorable conditions, meaning can enhance positive affect and enjoyment in mundane everyday living experiences (King and Hicks, 2012 ) and improve quality of life by engaging in meaningful activities (Iwasaki, 2007 ). Personal meaning is therefore an important source for well-being and a protective factor against mental health problems and suffering pertinent to this tumultuous time (Arslan and Yildirim, 2020 ; de Jong et al, 2020 ; Schnell and Krampe, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, burgeoning studies support that personal meaning serves as a protective factor against psychological distress amid the viral pandemic (Arslan and Yildirim, 2020 ; Gori et al, 2020 ; Yildirim et al, 2020 ). A renewed sense of personal meaning is suggested to help individuals cope with the traumas and grief over the loss of normalcy during these challenging times (de Jong et al, 2020 ; Lin, 2020 ; Schnell and Krampe, 2020 ). Furthermore, personal meaning has demonstrated to promote life satisfaction, healthy behaviors, and adaptive coping during COVID-19 (Gori et al, 2020 ; Lin, 2020 ; Minkkinen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%